2018
DOI: 10.5430/cns.v6n3p28
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between body image satisfaction, self-esteem and the academic behavior among the first and fourth year students in the faculty of nursing Tanta University

Abstract: Background: Body image is interrelated to a person's self-esteem. Misperception about one's body can be the cause of disturbed self-esteem, and this result in low academic achievement. The objective of this study is to explore the relation between body image satisfaction, self-esteem and the academic behavior among the first and fourth year students in faculty of nursing. Methods: A comparative description design was utilized for this study. Three tools used for this study: Tool 1, Part 1: Sociodemographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…As for gender differences, we found that a higher percentage of females reported body image concerns which is in line with other studies (2,31,39). It is possible that the higher rates of BID among females are attributable to the rapid weight gain (mainly in the form of fat) that occurs in this phase which could make girls more vulnerable than boys to social pressure to mold their bodies to fit the ideal of slenderness (39).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for gender differences, we found that a higher percentage of females reported body image concerns which is in line with other studies (2,31,39). It is possible that the higher rates of BID among females are attributable to the rapid weight gain (mainly in the form of fat) that occurs in this phase which could make girls more vulnerable than boys to social pressure to mold their bodies to fit the ideal of slenderness (39).…”
Section: Discussionsupporting
confidence: 90%
“…However, Yahia et al, in a study conducted among a sample of students (n=252) from the Lebanese American University in Beirut, Lebanon found that BSQ scores indicate that the 41% of students were worried about their body shape perception (30). While Elsherif and Abdelraof, , found that among nursing students in Tanta, Egypt 92.5% of students in their first year and 85.5% of those in their fourth year reported high body image dissatisfaction (31). Our study found lower restates two studies as they were conducted among university students while our study was among secondary school students.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that life satisfaction, self-esteem and body image may mitigate wellbeing in nursing students (Elsherif & Abdelraof, 2018;İlhan et al, 2016). Our findings suggest that life satisfaction and self-esteem have the most mediating effects on mental health for all students.…”
Section: Discussionsupporting
confidence: 51%
“…In this research field, we find studies that investigate the role of body image in academic performance, e.g., [ 8 , 14 ], while other studies place emphasis on weight status, mostly examining whether overweight and obesity disrupts academic functioning. The basic assumption is that excess weight can be related to lower academic achievement due to the stigmatized nature of obesity [ 15 ] and the possible impact of obesity on cognitive functioning [ 16 ].…”
Section: Introductionmentioning
confidence: 99%